Heat-Shock Protein 70 Overexpression in Adipose-Derived Stem Cells Enhances Fat Graft Survival. Issue 4 (April 2017) - Feng, Hao; Qiu, Lihong; Zhang, Teng; Yu, Houyou; Ma, Xianjie; Su, Yingjun; Zheng, Hui; Wang, Yong; Yi, Chenggang
Abstract : Background: Autologous fat grafting is a prevalent technique used for soft-tissue augmentation; however, the poor survival rate of the grafted tissue remains a drawback of this method. Although adipose-derived stem cells (ASCs) are an attractive candidate for enhancing graft retention, the poor posttransplantation viability of these cells limits their application. Here we investigated whether overexpression of the antiapoptotic protein heat-shock protein 70 (Hsp70) could enhance ASCs' therapeutic potential for fat transplant survival. Methods: Recombinant adenoviral vectors were used to overexpress Hsp70 in ASCs isolated from a healthy woman. The Hsp70 expression was assessed by quantitative real-time polymerase chain reaction and Western blot analyses. The adipose tissue granules aspirated from another woman were mixed with ASCs expressing green fluorescent protein (GFP)-tagged Hsp70 (group A) or GFP alone (group B), untreated ASCs (group C), and phosphate-buffered saline (group D). Fat mixtures were then injected subcutaneously into the backs of nude mice, and graft survival was compared after 3 months. Results: Adipose-derived stem cells transduced with recombinant adenoviral vectors exhibited significantly increased Hsp70 expression in vitro. Meanwhile, weight retention analyses demonstrated that fat grafts using the group A cell population exhibited significantly higher survival rates than the other treatment groups in vivo. Moreover, histological analyses revealed that fat grafts containing GFP-Hsp70–expressing ASCs yielded significantly lower levels of tissue fibrosis and fat cysts/vacuoles, higher capillary densities, and increased numbers of viable adipocytes than the control groups. Conclusions: Our data indicate that Hsp70 overexpression enhances the efficacy of ASC therapy by improving the survival and quality of the transplanted fat tissues.